2017
DOI: 10.2147/opth.s136500
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intravitreal injections on dry eye, and proposed management strategies

Abstract: Intravitreal injection of anti-vascular endothelial growth factor (anti-VEGF) agents has become a commonly used treatment method for a number of ophthalmic conditions, including age-related macular degeneration. Although anti-VEGF therapy has shown promising results for many patients, there are several aspects of its application that have not been thoroughly investigated. One of these is the development and/or escalation of concurrent dry eye syndrome. Many patients undergoing treatment are already predisposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…VEGF levels were reported to be elevated in the blood of diabetic patients, playing a key role in diabetes-related morbidity such as diabetic retinopathy, age-related macular degeneration, and a variety of cardiovascular diseases. In ocular surface diseases such as DED, VEGF is known as an inflammatory marker that impairs the surface epithelium of the eye ( 29 ). However, VEGF is also recognized as a pleiotropic factor with a broad effect on endothelial, neuronal, and glial behaviors ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…VEGF levels were reported to be elevated in the blood of diabetic patients, playing a key role in diabetes-related morbidity such as diabetic retinopathy, age-related macular degeneration, and a variety of cardiovascular diseases. In ocular surface diseases such as DED, VEGF is known as an inflammatory marker that impairs the surface epithelium of the eye ( 29 ). However, VEGF is also recognized as a pleiotropic factor with a broad effect on endothelial, neuronal, and glial behaviors ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…4 Povidone-iodine and antibiotics were blamed for the ocular surface effects after repeated intravitreal injections. 15 Intravitreal injection of anti-VEGF agents was not supposed to cause harm on meibomian glands. On the contrary, direct anti-VEGF injections into meibomian glands were reported as a treatment alternative.…”
Section: Discussionmentioning
confidence: 99%
“…These ocular surgeries are associated with DED in previous studies, with the incidence of post-cataract DED of 9–32% ( 21 , 22 ). Accumulating evidence also demonstrated that IVI was associated with deterioration of ocular surface health ( 20 , 23 ); TPPV contributed to the development of signs and symptoms of DED, and PRP induced the decrease in tear break-up time and Schirmer test value ( 24 ).…”
Section: Introductionmentioning
confidence: 99%